Statistical Coverage of Trade Finance : Fintechs and Supply Chain Financing - Lotte van Wersch, Cornelia (Washington, D.C. : International Monetary Fund, 2019)
Trade finance is the backbone of international trade for entities ranging from a small businesses to multi-national corporations. An estimated 80 percent of world trade relies on this form of finance (WTO, 2017). Despite its systemic importance and rapid growth, data availability is only partial. During the 2008 financial crisis, policy makers, notably the G20 recognized that the absence of comprehensive trade finance data posed a significant hurdle for policy-makers to make informed, timely decisions. This paper proposes a stand-alone dataset to reflect the scope, dynamic and recent innovations of the trade finance market to support macroeconomic policy analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet